2000
DOI: 10.1046/j.1537-2995.2000.40080988.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of in vivo and in vitro functions of fresh and stored human platelets

Abstract: It is possible to freeze platelets and retain in vivo efficacy if the cryopreservative DMSO is included in the preparation. In vitro responses were greatly reduced by all of the storage protocols, but it may not be necessary to retain 100 percent in vitro function to have a platelet substitute or storage product that functions satisfactorily in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…Rothwell et al (20) showed that platelets mounting 22% of the baseline aggregation function (after storage) were still able to provide adequate hemostatic function in an in vivo kidney bleeding model. No clinical studies have correlated in vitro results of aggregation tests with clinical effectiveness of platelet transfusions in actively bleeding patients or have studied the effect of transfused platelets with different aggregation responses on posttransfusion bleeding times.…”
Section: Discussionmentioning
confidence: 99%
“…Rothwell et al (20) showed that platelets mounting 22% of the baseline aggregation function (after storage) were still able to provide adequate hemostatic function in an in vivo kidney bleeding model. No clinical studies have correlated in vitro results of aggregation tests with clinical effectiveness of platelet transfusions in actively bleeding patients or have studied the effect of transfused platelets with different aggregation responses on posttransfusion bleeding times.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of refrigerated storage on coagulation properties of WB are virtually limited to coagulation proteins but not PLTs, 11 and there are no evaluations of integrated coagulation function. Storage effects have been studied extensively on refrigerated separated blood components of plasma and PLTs, suggesting that the integrity of plasma protein factors and PLT function may not fall below clinically useful levels during refrigerated storage until well beyond our current 48‐hour limit 11‐14 . Stimulated by the reports from the military and our observations in pediatric cardiac surgery, we wanted to learn the limits of storage of WB with regard to preservation of its beneficial hemostatic properties.…”
mentioning
confidence: 99%
“…Platelet sediments were washed twice in Tyrode buffer (pH 7.4) and then suspended in it (1 mL). Afterwards, platelets were frozen and stored according to previously published recommendations [21], [22].…”
Section: Methodsmentioning
confidence: 99%